English Speaking Learning through The "English Area" Program in Smk Negeri I Gorontalo - Sartin T Miolo; Emzir Emzir; Yumna Rasyid (JETL (Journal of Education, Teaching and Learning), 2017)
The purpose of this research is to know how the learning process speaks English through "English Area" Program at SMK Negeri I Gorontalo. The method used in this research is descriptive qualitative method. The data source is students in SMK Negeri I Gorontalo Class XI academic year 2015/2016. Data were collected using direct observation techniques on learning activities, interviews with teachers of English and students, documentation of learning outcomes and student achievement outcomes. The results show that the "English Area" program is well used to improve students' English speaking skills and can motivate them to use English. The conclusion is that English teachers at SMK Negeri I Gorontalo managed to create a way to make learners happy and interested in English speaking learning and their achievements increased.